Prompt treatment of disseminated HSV‐2 infection in a patient with compromised cellular immunity: A case of aborted hemophagocytic lymphohistiocytosis?. Issue 9 (25th May 2020) - Tsimpidakis, Antonios; Tsilingiris, Dimitrios; Remountaki, Eleni; Zouridaki, Eftychia; Rigopoulos, Dimitrios; Nicolaidou, Electra
Abstract: Recognition of unusual manifestations such as disseminated HSV or HSV‐related hemophagocytic lymphohistiocytosis among individuals with impaired cellular immunity and prompt treatment initiation are essential for a favorable outcome. Abstract : Recognition of unusual manifestations such as disseminated HSV or HSV‐related hemophagocytic lymphohistiocytosis among individuals with impaired cellular immunity and prompt treatment initiation are essential for a favorable outcome.